A new printed fractal right angled isosceles triangular monopole antenna for ultra-wideband applications - Manisha Gupta (Egyptian Informatics Journal, 2017)
In this present work, a different right angled isosceles triangular Microstrip patch antenna (RITMA) for ultra wideband (UWB) utilization is designed. The antenna presented is simple and small in structure. The antenna has a triangular patch with defected ground plane and a notch on the ground surface, which provides a usable bandwidth. By fracturing the antenna a significant improvement in return loss is seen, and good gain is obtained. Results of the proposed antenna show omnidirectional radiation behavior within the UWB frequency range.